Do auditors change their individual style? Examining the effects of client importance and competition on auditors' influence on earnings comparability in China - Chi, Wuchun (2023)
Individual auditor style implies that two client firms audited by the same individual auditors are likely to have more comparable earnings than two client firms audited by different individual auditors within the same audit firm. We investigate whether auditors in China change their individual style to cater to demands of clients that are of high importance and are located in a competitive audit market. Using a propensity score match approach, we find evidence of higher earnings comparability between a pair of client firms audited by the same individual auditors. However, in subsamples of client firm pairs that are of high importance or are located in a competitive audit market, we find earnings comparability of client firms audited by the same individual auditors diminishes. Our findings suggest that due to the influence of economic bonding in auditor–client relations in China, individual auditors change their style to cater to client demands.